2020
DOI: 10.1186/s12877-020-01695-5
|View full text |Cite
|
Sign up to set email alerts
|

Physical frailty and its associated factors among elderly nursing home residents in China

Abstract: Background: Evidence is scarce on the trend in prevalence of physical frailty in China; the primary purpose of this study was to identify the prevalence and correlates of physical frailty among older nursing home residents in China. Methods: Cross-sectional study in 20 nursing homes in Changsha, China. Physical frailty was defined based on the frailty phenotype including weight loss, low grip strength, exhaustion, slow gait speed, and low physical activity. Participants with at least three affected criteria we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
(63 reference statements)
3
14
1
5
Order By: Relevance
“…A study conducted in Bali, Indonesia reported a frailty prevalence rate of 43.3% compared with 69.3% and 55.6%, respectively, among individuals in Spain 19 ) and China. 20 ) However, the cohorts in these previous studies were significantly older than the cohort in the current study. We observed a significantly higher prevalence of frailty in a relatively younger population, a finding that requires further assessment to facilitate the early diagnosis and treatment of frailty.…”
Section: Discussioncontrasting
confidence: 49%
“…A study conducted in Bali, Indonesia reported a frailty prevalence rate of 43.3% compared with 69.3% and 55.6%, respectively, among individuals in Spain 19 ) and China. 20 ) However, the cohorts in these previous studies were significantly older than the cohort in the current study. We observed a significantly higher prevalence of frailty in a relatively younger population, a finding that requires further assessment to facilitate the early diagnosis and treatment of frailty.…”
Section: Discussioncontrasting
confidence: 49%
“…Based on the literature review that has been carried out, the following describes the condition of the elderly living in the institution. The majority of the elderly who live in nursing homes are aged 60 years and over, in general the elderly experience physical weakness including weight loss, easily experience fatigue when doing activities, experience a slowing of walking speed, and this condition will increase in the elderly who are older (3). Another weakness of physical conditions is that the elderly have decreased balance and flexibility of the body, agility, strength and endurance of the upper limbs, muscle strength and power, and joint mobility (2).…”
Section: Results and Discusionmentioning
confidence: 99%
“…Os estudos apontaram maior frequência de associação da fragilidade com o aumento da idade, especialmente entre os mais longevos, com idade ≥ 80 anos (DE LA RICA-ESCUIN et al, 2014;BORGES et al, 2015;DEN UIJL et al, 2015;LUO et al, 2015;TABUE-TEGUO et al, 2015;BUCKINX et al, 2016;2018a;2018b;CESARI et al, 2016;FERREIRA et al, 2016;KAEHR et al, 2016;THEOU et al, 2016;HASAN et al, 2017;LAWRENCE et al, 2017;MARTÍNEZ-VELILLA et al, 2017;OVERBEEK et al, 2018;GE et al, 2019;FURTADO et al, 2020;LIU et al, 2020). Estima-se que, para cada ano a mais de vida, haja aumento médio de 0,8% na pontuação da fragilidade (FHON et al, 2018).…”
Section: Discussionunclassified
“…Os resultados apontaram predomínio de fragilidade no sexo feminino (DE LA RICA-ESCUIN et al, 2014;DEN UIJL et al, 2015;LUO et al, 2015;TABUE-TEGUO et al, 2015;BUCKINX et al, 2016;2018a;2018b;CESARI et al, 2016;FERREIRA et al, 2016;KAEHR et al, 2016;THEOU et al, 2016;HASAN et al, 2017;LAWRENCE et al, 2017;MARTÍNEZ-VELILLA et al, 2017;OVERBEEK et al, 2018;MURUKESU et al, 2019;FURTADO et al, 2020;LIU et al, 2020). Essa condição é verificada tanto em idosas institucionalizadas, quanto entre as residentes na comunidade, apresentando prevalência de 69,6% e 60%, respectivamente (AUGUSTI et al, 2017;MELO et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation